Edukasi Kesadaran Remaja tentang Pentingnya Pendidikan Seksual dan Etika Pergaulan Sehat di SMP 2 Bireuen - Nurhayati Nurhayati; Cut Nanda Fermita; Ledyana Fitriani; Musrizal Musrizal; Zahraini Zahraini; Umar Iskandar (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
Many adolescents have not yet mastered sexual education and social boundaries at the junior high school level. Several students are unable to distinguish between safe and dangerous social behaviors. The community service program was aimed at adolescents to improve knowledge and awareness about sexual education, reproductive health, and social norms. This program was conducted at SMP Negeri 2 Bireuen with 33 students of class IX, consisting of 20 females and 13 males. The method used was a combination of interactive lectures, group discussions, question-and-answer sessions, video media, and evaluation using a one-group pretest-posttest design. The results showed that there was a significant difference in the level of knowledge before and after the intervention program. The average pretest score was 56.3, while the posttest average score was 82.7 with an increase of 26.4 points. In addition, 87.9% of the participants were able to answer correctly about the material delivered and showed a more positive attitude towards the effect of unhealthy relationships on health, with a p-value <0.05. This program effectively increases knowledge and awareness about sexual education and social norms among adolescents in SMP Negeri 2 Bireuen. It is recommended that this program be conducted periodically with active participation from schools and parents.